Retrospective case-series of Paecilomyces lilacinus ocular mycoses in Queensland, Australia - Turner, Liam Daniel (BMC Res Notes, 2015)
BACKGROUND: The purpose of this study was to report: (1) the varying presentation of Paecilomyces ocular infections arising in Queensland; (2) the significance of immunosuppression as a primary determinant of disease; (3) the outcomes of voriconazole use; and (4) the ongoing need for both surgical and medical management of this devastating fungal infection. METHODS: A retrospective case series of 21 culture proven individuals participated in this series and were identified via a review of the pathology reporting system utilized in the Queensland public health system. All culture proven individuals were subjected to a systematic chart review. RESULTS: The primary risk factor for Paecilomyces lilacinus infection is immunosuppression with 81.25 % of individuals being on some form of immunosuppression (i.e. systemic or topical). Of the cases 71.43 % had an intact epithelial surface at the time of diagnosis, and 76 % had no previous ocular history. The final visual outcomes were nine cases with HM vision or worse, three cases with 6/48–6/60 vision, three cases 6/12–6/24, and six cases with 6/12 vision or better. Despite voriconazole use rates of greater than 80 %, protracted and poor treatment outcomes continue to be commonplace. CONCLUSIONS: Paecilomyces lilacinus is a filamentous fungus that has a predilection for immunosuppressed individuals. Despite in vitro and case reports demonstrating the effectiveness of voriconazole poor outcomes continue to be seen.